The conflict resolution toolbox : models and maps for analyzing, diagnosing, and resolving conflict - Furlong, Gary T. (John Wiley & Sons, Inc., 2020)
"Since the first edition of this book was published in 2005, technological and scholarly advances have made significant contributions to our understanding of how we communicate and engage with each other. This Second Edition recognizes the important research done over the last 15 years in the fields of neuroscience, neuropsychology, and behavioural economics with two new models that look at the deeper patterns and biases our million-year-old brains use to connect and make decisions. It also recognizes the value that the tools in the first edition brought to practitioners everywhere, retaining and refining the models that have been recognized as powerful and useful tools in resolving conflict between people. The technology we all use to communicate may have changed, but human nature and our experience of conflict is still very much with us. Imagine for a moment that you are faced with a conflict. Imagine, for example, that your new neighbour loves to have guests over many nights of the week until the early hours of the morning, keeping you up with the noise. When you talk to your neighbour, he laughs and tells you, "Loosen up, have some fun. Come and join us if you want! You need to enjoy life more!" You go home after the conversation and get increasingly angry. You think about how insensitive he is, how little he cares for other people. You begin to think that he may actually be retaliating for the fact that your dog barks every now and then, which he complained about once. Given how you see the problem, you vow to call the police the next time he has a party during the week. This conflict is headed for a significant escalation. We are all faced with conflict situations in many aspects of our lives, whether in our personal life, in the workplace, or with just about anyone we meet. Given how common conflict situations are and how frequently we deal with conflict, you would think that we'd all be pretty good at handling conflict and building, or re-building, relationships"- Resumé vydavatel
Includes index.
Keywords: management konfliktů; mediace; conflict management; mediation; elektronické knihy; příručky; electronic books; handbooks and manuals